The effect of the supportive program on the anxiety of mothers of infants with gastrointestinal anomalies - Aleheh Seyedrasooli; Jamileh Malakouti; Mahnaz Jabraeili; Soraya Heykalabadi; Morteza Ghogazadeh (Tehran University of Medical Sciences, 2020)
Background & Aim: The birth of an abnormal infant and his admission to the intensive care unit creates various mental health effects on their mothers and increases their anxiety. The goal of this study was to determine the effect of supportive programs on the anxiety of mothers of infants with gastrointestinal anomalies. Methods & Materials: This randomized controlled clinical trial was conducted in the Neonatal Intensive Care Unit in Tabriz, Iran. In this study, 50 mothers who had infants with gastrointestinal anomalies were assigned randomly to control and intervention groups. The control group received routine care, and the intervention group received special supportive care: emotional, informational, self-esteem, and caring support during four sessions for a 45-minute duration. Maternal anxiety was measured using the State-Trait Anxiety Inventory. Data were analyzed by using SPSS/19 and paired-sample and independent t-test. Results: The results showed that both groups of mothers had high-level anxiety in the pre-test. In the post-test, the mothers' anxiety level in the intervention group was significantly lower than the control group. ANCOVA test to compare the mean difference of state and trait anxiety in both groups showed that these changes were statistically significant (P<0.001). Conclusion:  This study tried to introduce a protocol to protect mothers of gastrointestinal anomalies, which could be used in the Neonatal Intensive Care Unit. The findings of this study also highlighted the importance of supporting one of the fundamental principles of family-centered care. Based on the outcomes of this research, emotional, informational, self-esteem, and caring support could reduce the mother's anxiety.